Diagnóstico del comportamiento organizacional de las empresas comercializadoras de productos lácteos en Portoviejo para la mejora de su desempeño empresarial - Bravo Bravo, Mónica Lourdes (2016)
This work was done in the city of Portoviejo, located geographically and to 01 degrees, 3 minutes, 8 seconds south latitude, and 80 degrees, 27 minutes and 2 seconds west longitude. It limits the north, with Rocafuerte, Sucre, Bolivar and Junín cantons; south, with the canton Santa Ana; west with the Montecristi and the Pacific Ocean and the east with Pichincha and Santa Ana cantons, whose main objective was to make the diagnosis of Organizational Behavior trading companies of dairy products, to contribute to improving their performance to identify recurring internal and external factors that are immersed in the activities performed institutions. The companies investigated in this project were Lacycon and Pura Crema, in these institutions deductive methods were applied to identify the main shortcomings that affect the performance of staff within the institution, for this, a survey was conducted to verify the real problems existing in both companies. the inductive method in which a tab observation which determined what factors affect work behavior of workers, the same information that allowed us to obtain and analyze the results and diagnosis were used was also applied, and the same a proposal reflected way was presented in the solution of the identified problem, proposing improvements to each recurring factor involved in different organizations and worker performance in order to obtain better job performance, higher productivity and above all create a harmonious environment and responsible development of them.